2012
DOI: 10.5137/1019-5149.jtn.5855-12.1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intracerebroventricular injection of beta amyloid peptide (1-42) on caspase-3 activity, lipid peroxidation, nitric oxide and nos expression in young adult and aged rat brain

Abstract: AIm: Intracerebroventricular (icv) administration of beta amyloid peptide (Aβ) in rats can be used to model certain aspects of Alzheimer disease (AD).The purpose of this study was to examine the effects of intracerebroventricular Aβ (1-42) peptide injection on caspase-3 activity and expression of nNOS and iNOS, malondialdehyde (MDA), glutathione (GSH) and NOx in the hippocampus, temporal cortex and parietal cortex. mAterIAl and methOds: Groups were defined as 1) young adult control, 2) Aβ (1-42) injected young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 13 publications
6
19
0
Order By: Relevance
“…In our study, Aβ administration increased lipid peroxidation as shown by a higher level of MDA and lowered SOD activity as an antioxidant system. These results support previous findings that reported significantly increased level of MDA in rodents after injection of Aβ (Cetin et al, 2013). However, there are much controversy on SOD changes in AD models.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, Aβ administration increased lipid peroxidation as shown by a higher level of MDA and lowered SOD activity as an antioxidant system. These results support previous findings that reported significantly increased level of MDA in rodents after injection of Aβ (Cetin et al, 2013). However, there are much controversy on SOD changes in AD models.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, intracerebroventricular administration of Aβ showed a significant impairment in learning and memory, which was in line with other studies (7,47).…”
Section: Discussionsupporting
confidence: 80%
“…Previous research also confirmed that cell apoptosis after epilepsy was related to overexpression of NO, which demonstrated that iNOS was more closely related with apoptosis (22). Another study demonstrated that a selective iNOS inhibitor could significantly reduce the expression of caspase-3 (23). The results of the current study suggested that geniposide treatment did not significantly affect iNOS mRNA expression in mouse epilepsy.…”
Section: Discussionsupporting
confidence: 74%